Role of nanocellulose geometric structures on the properties of green natural rubber composites - Milanta Tom; Sabu Thomas; Bastien Seantier; Yves Grohens; Mohamed Pulikaparambil Kochaidrew; Ramakrishnan Subramanian; Tapas Ranjan Mohanty; Henri Vahabi; Hanna Joseph Maria; Jibin Keloth Paduvilan; Martin George Thomas (eXPRESS Polymer Letters, 2024)
The augmented demand for sustainable nanocomposites has paved the way to explore naturally derived materials. Nanocellulose, with its bountiful sources and inherent properties, ranks top in the list of biofillers with a perspective of reducing the carbon footprint. A systematic study is required to understand the reinforcing effect of various types of nanocellulose. In the present work, we selected three types of nanocellulose, i.e., cellulose nanocrystal (CNC), cellulose nanofiber (CNF) and microfibrillated cellulose (MFC), to investigate the effect of geometrical structure on the properties of unvulcanized natural rubber (NR). Incorporating these fillers improved the tensile strength and modulus of natural rubber films significantly through reinforcement via filler network structure. The reinforcing effect of CNF was found to be higher compared to CNC and MFC, where an increase of 3.85 MPa in tensile strength from the neat sample was obtained. More uniform dispersion was evident through transmission electron microscopy, atomic force microscopy and Raman imaging for CNF in the rubber matrix. The structural properties were determined using Raman spectra and X-ray diffraction. The rheological studies revealed a good interaction between filler and NR. The work presented comprehensively compares different types of nanocellulose as reinforcing filler in NR matrix, which will help the researchers select an ideal type for their specific application and, thus, the proper usage of renewable resources, leading to sustainability and a circular economy.